Budgeting and Analysis of Social Service Providing Institutions: the Case of Care Homes - Miškinienė, Renata; Nariūnaitė, Andželika; Basiulis, Katažyna; Straigė, Milda (Buhalterinės apskaitos teorija ir praktika, 2024)
One of the main functions of social protection is the provision of social services to people who need them. In today’s society, the need for social services tends to increase and needs to be adequately funded. However, the issues of the management and financing of these services have not been sufficiently investigated. In order to fill this gap, this article examines the financing arrangements for social services. It also analyses and evaluates the preparation and implementation of the budget of the institution providing such services. The object of the study is the budget for 2020-2022 of one of the institutions providing social services – care homes. The aim of the study: after examining the nature of social services and the arrangements for their management and financing, to assess the arrangements for preparing the budget of the care home and to analyse it budget for the period 2020-2022. The study found that the projected revenue and cost budget of the care home is quite different from the actual revenue and cost of the institution. The study identified the reasons for these variances and made suggestions for improving the preparation of the budget project with a view to reducing the variances between planned and actual amounts in future.